Borane Catalyzed Selective Diazo Cross‐Coupling Towards Pyrazoles. Issue 4 (8th December 2021) - Dasgupta, Ayan; Pahar, Sanjukta; Babaahmadi, Rasool; Gierlichs, Lukas; Yates, Brian F.; Ariafard, Alireza; Melen, Rebecca L.
Abstract: Decomposition of donor‐acceptor diazo compounds leads to the formation of reactive carbene intermediates. These can undergo a wide variety of carbene transfer reactions to yield synthetically useful products. Herein, we report a selective borane catalyzed cyclization reaction from the combination of two different diazo compounds to afford N‐substituted pyrazoles. The selective decomposition of the more reactive α‐aryl α‐diazoester and subsequent reaction with a vinyl diazoacetate produces N‐alkylated pyrazoles in a regioselective manner. Catalytic amounts of tris(pentafluorophenyl)borane (10 mol%) were employed to afford the pyrazole products (36 examples) in yields from 59 to 80%. Extensive DFT studies have been undertaken to interpret the mechanism for this reaction which was found to go through two tandem catalytic cycles, both catalyzed by B(C6 F5 )3 . Abstract :